Evolution of business models in French 'Pôles de compétitivité': the role of intermediaries in horticultural varietal creation - Isabelle Leroux; Paul Muller; Béatrice Plottu; Caroline Widehem (European Regional Science Association (ERSA), 2014)
A device central to the French cluster (Competitiveness pole) policy is the financing of collaborative projects aimed at enhancing the innovation capacities of firms. In turn, increasing in innovation capacities give rise to new business opportunities that firms only can seize by evolving their business model. Business model accounts for the ways value is developed, delivered and captured by firms (Chesbrough 2007). However, internal and external constraints may impede their evolution. Those constraints are particularly harmful for SME: 1. Firms must dedicate specific resources to innovate their business models (Helfat and Winter 2011) but SME may arguably face strong constraints on devoted resources. 2. The capacity of innovating a business model may require firms to be able to influence local collective rules (Sabatier et al. 2012). However, unless being locally pivotal, a SME's influence may be too low to enable it to exert a significant influence on those rules, especially when significant business model innovation is at stake. Our paper discusses the role played by local institutions while addressing the issue of business model evolution in SME. It specifically focuses on the governing bodies of Competitiveness poles. We argue that those governing bodies play a central role in releasing stakeholders from business model evolution impediments as they act as innovation intermediaries. We base our research on the study of BRIO, a publicly funded collaborative project undertaken by members of Vegepolys, a Competitiveness pole located in French Pays-de-la-Loire Region and dedicated to specialized vegetal industries. Horticultural SMEs, INRA and the University of Angers have been involved in this project. It has aimed to design new tools and methodologies for creating new varieties of plants through varietal creation. Our case reveals that Vegepolys' governance body has played a key role in the success of the project by translating scientific (produced by INRA researchers) into technological knowledge and by being a go-between facilitating the establishment of new collective rules.
Keywords: L10; O31; Q16; 330